The differences in physical activity levels in preschool children during free play recess and structured play recess - Megan L. Frank; Anna Flynn; Gregory S. Farnell; Jacob E. Barkley (Elsevier, 2018)
Background/Objective: Physical activity (PA) is important in reducing childhood obesity, yet a majority of children are not meeting PA guidelines. Schools have been identified as a place to promote childhood PA. The purpose of this study was to determine the best type of physically active recess period to increase preschool-aged children's PA. Methods: PA was measured via accelerometers in preschool-aged children (n = 29) during three, 30-min recess conditions (control; structured play; free play) on separate school days. Tertile splits were performed based on PA during the free play condition and children were divided into three groups: highly, moderately and least active. Results: For the aggregated sample, children were more (p ≤ 0.001) active during the free play (1282 ± 662 counts. min−1) and structured play (1416 ± 448 counts. min−1) recess versus the control condition (570 ± 460 counts. min−1) and activity was not different between the free play and structured conditions. However, children who were the most active during free play (1970 ± 647 counts·min−1) decreased (p ≤ 0.05) activity during structured play (1462 ± 535 counts·min−1), whereas children who were moderately active (1031 ± 112 counts·min−1) or the least (530 ± 239 counts·min−1) active during free play increased activity during structured play (1383 ± 345 counts·min−1 moderately active, 1313 ± 413 counts·min−1 least active). Conclusion: Providing a physically-active recess period will contribute to preschool-aged children meeting the recommended PA guidelines; however, different children may respond in a different way based upon the structure of the recess period.